Microplasticity of subsurface layers of diamond-like semiconductors under microindentation - Nadtochiy, V.A.; Alyokhin, V.P.; Golodenko, M.M. (Физика и техника высоких давлений, 2005)
Experimental confirmations of the influence of the free surface of a chip on processes of plastic deforming under indentation such as a decrease of the effective activation energy of dislocations with reduction of load on the indenter and a considerable decrease of temperature of the beginning of polygonization processes, when annealing microhardness rosettes in the field of small impresses, are obtained. A possibility of dislocation motion by means of creeping at temperatures lower than brittleness threshold temperature was shown on the example of GaAs.